Practitioners' Perspective About Support Services Offered to Inclusive Students at Special Education and Rehabilitation Centres - Eren Yenigün; Serhat Odluyurt (Anı Publishing, 2020)
The aim of this research is to determine the support services and their needs which are given by the teachers working in a Special Education and Rehabilitation Centres (SERC) to the students who continue to inclusion. With this aim, semi-structured interview forms are prepared, acquired data are analyzed descriptively. The participants are constituted by 13 females and two male teachers working in a SERC. The teachers, who say that they find difficulty in providing academic skills to the inclusive students, its evaluation or how to approach it, stated that they have not been provided sufficient support services on this subject. The teachers who participated in this research, saying that regarding the responsibility of the inclusive schools, which the students go to, are preparing appropriate Individualized Education Program (IEP), offering support education, helping with the problems; stated that the school should inform the peers and should never discriminate the children whatsoever. Teachers expressed that the SERC are seen as units for presenting support to the inclusive students, and as units for offering support aimed at academic, personal or behavioral problems.